Assisted vs. Guided Handwriting: a current approach to an old problem - Kalantzis, Nikolaos; Gidogiannos, Leonidas Dimitrios (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
A study carried through to determine which writer’s features are apparent in the end result of a guided signature. The examination included 14 participants in total, one of which was left handed. To fulfill its scope, 9 writing features of 20 supported and 20 guided signatures for each participant were examined and the results were related to previous research on the matter of guided signatures and handwriting. This study demonstrated that guided signatures yield a significant volume of writing features belonging to the guider, providing robust evidence on the subject of guided signatures. Several limitations were highlighted and proposals for future studies were also made.
Keywords: podpis wspomagany; pomoc w pisaniu; podpis sterowany